Asperulosidic acid inhibits the PI3K/Akt/NF-κB pathway to suppress endotoxin-induced uveitis - Yong Du; Jing Lu; Lujia Feng; Long Zhao; Ping Wu; Yuxia He; Linbin Zhou; Xing Wang; Hui Peng (Frontiers in Medicine, 2025)
IntroductionUveitis, a severe inflammatory disease affecting the uvea, is associated with visual impairment and irreversible blindness. Asperulosidic Acid (ASPA), derived from Hedyotis diffusa, is known for its notable anti-inflammatory and antioxidant characteristics.MethodsThe present study explored the potential anti-inflammatory effects and the fundamental processes of ASPA by injecting it or a placebo into the vitreous of rats with endotoxin-induced uveitis (EIU). The severity of the disease was assessed using clinical scores obtained through slit lamp examination. The study involved the examination of protein concentrations and cell count in the aqueous humor (AqH), the detection of inflammatory mediators expressed in the retina. We evaluated the expression levels of various proteins, including the tight junction protein ZO-1, the endothelial marker VE-cadherin, and the key inflammatory mediators NF-κB and its phosphorylated form, along with the regulatory proteins IκB-a and IKK in their phosphorylated and non-phosphorylated states.ResultsASPA treatment significantly reduced the clinical score of EIU, including inflammatory leukocyte penetration, protein accumulation, cellulose-like exudates, the expression of ICAM-1, IL-6, MCP-1, and TNF-α in the AqH; and adhesion of leukocytes. The activation of the PI3K/Akt/NF-κB pathway was observed in EIU. Nevertheless, pretreatment with ASPA significantly suppressed the release of ICAM-1, TNF-α, MCP-1, and IL-6.DiscussionASPA may play a role in suppressing LPS-induced inflammation by obstructing the activation of the PI3K/Akt/NF-κB signaling pathway. As a result, ASPA has shown the capacity to significantly reduce immune inflammation.